Design and development of motorbike roof shield for delivery service - Nalliah, Nivishan; Abd Anasghaneem, Abd Aziz; Juliawati, Alias; Nasrul Azuan, Alang (2021)
Due to the irregular Malaysian climate, many motorcycle owners especially delivery riders, experience difficulties during the rains and disrupt services.